CONFRONTANDO O DUMPING SOCIAL : ANÁLISE DA LEGISLAÇÃO NACIONAL DE COMBATE E SEUS IMPACTOS NA LIBERDADE ECONÔMICA - Sanches Aguera, Pedro Henrique (2023)
This article addresses the phenomenon of social dumping, focusing on the regulation of the subject. It begins with an analysis of the impact of globalization as a starting point for its practice in the economy. Next, the different types of dumping are presented, aiming to provide a broader understanding of the context in which the phenomenon is inserted, as well as the essential elements for its characterization. Focusing on the national legal scope and its connection with the international legal order, the creation of the GATT and later the WTO are discussed, highlighting the relevance of the rights of human dignity in this theme. In addition, the article addresses the problem of implementing excessive economic freedom, highlighting the lack of adequate interaction between these measures and the practice of competition in the global market. Through a deductive approach, based on descriptive and exploratory analyses, using documentary and doctrinal sources, it is concluded that the adoption of good regulatory practices, such as the creation of laws that encourage the socially responsible action of entrepreneurs, is crucial to protect workers' rights in this context.